Study on the formation and dewatering process of the surface filter cake of geotextile on the lateral boundary of geotextile tubes under constant flow grouting - Sheng, Mingqiang; Zhu, Qixin; Huang, Faming; Zou, Chun; Gao, Yang; Liu, Xinxin (Frontiers in Earth Science, 2024)
In this article, physical model test and numerical simulation are used to study the formation of filter cake and the filtration performance of the geotextile on the lateral boundary of the ultra-fine tailings grouting geotextile tubes from macro and micro levels. At the macro level, the effects of different grouting flow rates and tailings slurry mass concentrations on the surface filter cake formation and the dehydration performance of geotextile on the lateral boundary of the geotextile tubes were analyzed. At the micro level, the use of CFD-DEM method for fluid and particle of two-way coupling numerical simulation research, lateral drainage boundary of superfine tailings in tubes filter cake forming process is analyzed. The research shows that the increase of grouting flow rates and tailings slurry mass concentrations will make the thickness of filter cake great and the structure more compact, which will lead to more serious silting of the surface layer of geotextile and greatly reduce the dehydration performance; The numerical simulation results regularity is consistent with the results regularity of physical model test on the formation of filter cake on geotextile surface of geotextile tubes: the larger the slurry inlet speed and particles concentrations, the more complete the formation of filter cake on geotextile surface, the denser the cake structure, and the less tailings loss. By studying the effects of grouting flow rates and slurry mass concentrations on the surface filter cake formation and tubes dehydration, this article aims to find suitable slurry filling construction conditions and explore the main influencing factors caused by dehydration and consolidation of ultra-fine tailings grouting geotextile tubes, so as to provide some help for the subsequent flocculating of ultra-fine tailings to solve the problem of surface drying and internal wetting of geotextile tubes.